Christian fundamentalism and the culture of disenchantment - Maltby, Paul (Univ. of Virginia Press, 2013)
Creed and critique -- Fundamentalist history, postmodern contingency -- End times fiction and the ironic reader -- Fundamentalist exclusivism, radical democracy -- Fundamentalist dominion, postmodern ecology -- Evangelical painting and the ironic spectator -- Disenchanted Christianity